Sobre marcos conceptuales alternativos - Rolleri, José Luis (Disputatio, 2020)
This paper critically analyzes the question of how two conceptual frameworks could be established as each others alternatives. To settle this question is very important for some conceptualist hypothesis about scientific theories. Such hypothesis make sense only if there are different conceptual frameworks, or theories, or paradigms, which are alternative in a relevant epistemological way.  One central conceptualist hypothesis asserts that our claims of how the physical word is are put forward from some conceptual framework or other which in any case is or is related to a given conceptual framework of a scientific theory. That kind of epistemological hypothesis has been criticized along with their strong ontological consequences. Here such criticisms are discussed, and the possible routes of responding that question are analyzed.